From Bench to Bed: The Current Genome Editing Therapies for Glaucoma - He, Meihui; Rong, Rong; Ji, Dan; Xia, Xiaobo (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is a group of optic neuropathies featured by degeneration of retinal ganglion cells and loss of their axons in the optic nerve. The only currently approved therapies focus on lowering intraocular pressure with medication and surgery. Over the previous few decades, technological advances and research progress regarding pathogenesis has brought glaucomatous gene therapy to the forefront. In this review, we discuss the three current genome editing methods and potential disease mechanisms of glaucoma. We further summarize different genome editing strategies that are being developed to target a number of glaucoma-related genes and pathways from four aspects including strategies to lower IOP, neuroprotection, RGC and optic nerve neuro-regeneration, and other strategies. In summary, genome therapy is a promising therapy for treating patients with glaucoma and has great potential to be widely applied in clinical practice.